2018
DOI: 10.1007/s12639-018-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a new immunochromatographic test in detection of Toxoplasma gondii in cancer patients

Abstract: Screening of toxoplasmosis in cancer patients is mandatory especially before starting treatment to guard against life-threatening disseminated disease. Diagnosis of toxoplasmosis rely mainly on serology. The most widely used method for detection of anti-Toxoplasma gondii (T. gondii) antibodies is the enzyme linked immunosorbent assay (ELISA), being available and reliable. Immunochromatographic tests (ICT) attracted a lot of attention recently being one of the high quality, rapid and easy to perform tests. Avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…Kappas test showed that the diagnostic methods significantly detect IgG. Similar ascertains were made in a similar study carried out by other scholars [3,18].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Kappas test showed that the diagnostic methods significantly detect IgG. Similar ascertains were made in a similar study carried out by other scholars [3,18].…”
Section: Discussionsupporting
confidence: 85%
“…The sensitivity and specificity of Rapid ICT in the study was 46.7% and 81.7% respectively. This result is slightly at variance with findings from similar studies where sensitivity and specificity were found to be 62.2% and 96.3% [22], 97.2% and 100% [3], 61.5% and 80% [9], 87.5% and 74% [18] respectively in comparing the rapid ICT with ELISA. These studies all ascertained that rapid ICT test demonstrated optimal analytical sensitivity and specificity for Toxoplasma-IgG testing and can be used in detecting T. gondii antibodies especially chronic infections [3,18,22] The low sensitivity value reported in this study may be due to false positive results.…”
Section: Discussioncontrasting
confidence: 84%
“…Its ease of application and rapidity of test results with no special equipment required makes the ICT suitable for field application. In toxoplasmosis, this technology has been used to diagnose human (Lévêque et al, 2019;Taha et al, 2019;Wassef and Abdel-Malek, 2019) and animal cases (Khan and Noordin, 2019). ICT has been shown to have a high agreement with ELISA in terms of sensitivity and specificity (Terkawi et al, 2013;Ybañez, Kyan and Nishikawa, 2020).…”
Section: Immunochromatographic Tests (Ict)mentioning
confidence: 99%
“…Several serological procedures have been extensively used, including Sabin-Feldman dye test (DT), indirect fluorescent antibody test (IFA), direct agglutination test (DAT), differential agglutination test (HS/AC test), latex agglutination and indirect agglutination tests (LAT), immunosorbent agglutination assay (ISAGA), immunochromatographic tests (ICT), enzyme-linked immunosorbent assay (ELISA), IgG avidity test, and Western blot (WB) analysis [ 77 , 91 , 92 ] (Table 2 ). However, they are not all routinely performed by most hospital-based clinical laboratories, because of excessive cost, lack of experienced personnel and sensitivity, specificity, and interpretation deficiencies.…”
Section: Methodsmentioning
confidence: 99%